GUIDED IMAGERY RELAXATION TECHNIQUES REDUCE PATIENT'S PAIN POST ATTACK HEART [TEKNIK RELAKSASI IMAJINASI TERBIMBING (GUIDED IMAGERY) MENURUNKAN NYERI PASIEN PASCA SERANGAN JANTUNG] - Rizka Febtrina; Winta Febriana (Universitas Pelita Harapan, 2019)
Heart attack or commonly referred to as acute myocardial infarction (AMI) is a life-threatening condition that is marked by the formation of local necrotic area within the myocardium. The usual condition felt by the patient after heart attack is the pain in the chest. Pain is a sensation of individual discomfort felt by the patient. If the pain is not solved it will result in an uncomfortable to the patient either physically or psychologically. One of the interventions that can be used to reduce pain is a guided imagery relaxation technique (Guided Imagery). The purpose of this study was to determine the effect of guided imagery relaxation techniques (Guided Imagery) to decrease the patient's pain after a heart attack at the Flamboyan Lounge Arifin Achmad Hospital in Riau province. The samples in this study were patients with AMI medical diagnoses who experienced moderate pain. The type of this research is quantitative design that is used is quasi experiment